Analisis Faktor Yang Mempengarugi Permintaan Kredit Pemilikan Rumah - Ahmad Zainur Rozikin; Amin Wahyudi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Rapid technological developments have led to rapid population growth, which in turn has increased the demand for various types of properties and homes. This increase in demand is very important because property and houses are people's basic needs, but the land available for development is increasingly limited. With population growth continuing to increase in Indonesia, demand for housing is also increasing. Every individual needs a house as a place to live, protection, and a place to gather with family. The aim of this research is to investigate the factors that influence mortgage demand in the Puspa Asri housing complex in Plalangan, which is located in Jenangan District, Ponorogo Regency. The research method used is a qualitative method, which produces descriptive data in the form of observed behavior, speech or writing. This research methodology focuses on library research or library research, which involves analyzing sources such as books, articles and other sources relevant to the research topic. The results of this research are that when choosing a place to live, people do not only consider their income level. People tend to prefer housing subsidies based on personal needs, such as locations close to work and schools, as well as good accessibility to meet their daily needs. In addition, people currently prioritize long-term ownership by buying a house on credit, even though the payment term is longer, rather than renting a monthly fee.